Power and Possession: Analyzing Control in Robert Browning's 'My Last Duchess' and Its Reflections in Modern Society - Hassan, Ishraq (Integrated Journal for Research in Arts and Humanities, 2024)
Robert Browning’s My Last Duchess is among the most popular monologues of the Victorian era and a perfect case study for examining the depictions of power, possession, and control. From the face value, it is apparent from the poem that power resides with those who possess wealth and title. Additionally, those in power can become extremely controlling to the detriment of those subject to them. In this case, the duke embodies a controlling and possessive individual in a position of power. The main contrast between the poem and modern society is that it would not be possible for an individual today to commit murder with impunity regardless of wealth and power. The rationale is that in many societies, the power resides with the people, and the leaders are considered to serve the interests of the people. Even the dictators face the wrath of their subjects if they commit such acts. Additionally, even the most conservative societies today do not treat women the same way they were treated in the Victorian era. However, cases of female domination and control are still rampant. Domestic violence in modern society may reflect the need for some men to dominate and control their women with such desires that lead them to commit violence against them. However, such incidences are an oddity as opposed to the Victorian era, when they could have been common.